The Impact of Green Business Ethics and Green Financing on Sustainable Business Performance of Industries in Türkiye: The Mediating Role of Corporate Social Responsibility - Alay, Hazal Koray; Keskin, Abdulkadir; Şen, Gülaçtı; Kayalıdereden, Didem; Berber, Şayan; DEVECİYAN, MERİ TAKSİ (MDPI, 2024)
The purpose of this research is to understand the relationship between green business ethics, green finance, and sustainable business performance, and to evaluate the role of corporate social responsibility (CSR) in this relationship. The impact of the damage inflicted on nature's functioning order is being felt much more strongly today. In light of these realities, companies must emphasize sustainability principles not just out of financial concerns but as a result of corporate social responsibility. In this context, focusing on the role of corporate social responsibility in sustainable business performance is the main goal of this research. Quantitative research methods, specifically the cross-sectional survey method, were employed for data collection and analysis. For this purpose, a convenience sampling method was used to select 427 white-collar employees working in industries operating in T & uuml;rkiye as the sample for this study. The data collected through surveys were analyzed using the AMOS 24 statistical program. The findings underscore that green business ethics and green finance have a significant impact on corporate social responsibility and sustainable business performance. Additionally, it was determined that corporate social responsibility plays an intermediary role in shaping sustainable business performance. These findings are expected to provide an important foundation that can guide both employees and managers in developing awareness about green policies and sustainability, emphasizing the importance of green policies in working life.
Keywords: Corporate Social Responsibility; Green Business Ethics; Green Finance; Sustainable Business Performance